Fitossociologia do compartimento arbóreo da mata ribeirinha no rio Vacacaí, Rio Grande do Sul, Brasil - Figueira, Maurício (2014)
The present study aimed to analyze the tree compartment of the riverside forest in Vacacaí river and investigate the relationship between the species and the characteristics of soil and topographic variables in an environmental gradient. The regeneration, stratification and dispersion guilds for two sectors of the tree community were also analyzed.A plot of 100 x 100 m was installed in the fragment, subdivided into 100 sampling units (SU) of 10 x 10 m. Each SU has been ranked sector Upper Sites (US) or Low Sites (LS). The SUs that had good drainage were considered in US, totaling 72 SUs, and where there was evidence of possible environmental disturbances such as periodic flooding and elevation of groundwater, were classified as LS, totaling 28 SUs. All individuals with diameter at breast height ≥ 5 cm were inventoried. In each SU were collected samples of soil and topographic variables, such as elevation range and average elevation. To verify the relationships between environmental variables and the distribution of individual trees, we used the canonical correspondence analysis (CCA) was used. The survey recorded 1729 individual trees belonging to 41 species from 34 genera and 20 botany families. The species highlighted in Importance Value for the survey were Actinostemon concolor (Spreng.) Müll. Arg. (51%), Sebastiania commersoniana (Baill.) LB Sm. & Downs (46,7%), Inga vera Willd. (31%), Pouteria gardneriana (A. DC.) Radlk. (29,7%) and Casearia sylvestris Sw. (21,3%), accounting for 59,9% of this index. A canonical correspondence analysis (CCA) indicated that there is a correlation between soil and topographic variables with woody vegetation. Only four variables: the CCA were significant, average elevation, elevation range, pH and CEC. Thus, these variables stood out as good indicators of floristic and structural variations, being responsible, in part, the explanation of the formation of the two sectors. These were differences in wealth, in the structure and composition of guilds and this may be due to a different historical process of environmental change in each sector.